Three new records of asteroids (Echinodermata: Asteroidea) from Peru - Hooker, Yuri (2011)
The aim of this work is to present three new shallow water (4 - >50 m) records of asteroids (Echinodermata: Asteroidea) for the Peruvian fauna: Astropecten regalis Gray, 1840, Paulia horrida Gray 1840 and Meyenaster gelatinosus (Meyen, 1834). Astropecten regalis geographical distribution is known that ranges from Gulf of California to Panama, this discovery extends its distribution to Mancora, Peru. Paulia horrida is known from Baja California to Isla Cocos, Costa Rica, and this record extends its southern distribution limit to Punta Sal, Peru. Meyenaster gelatinosus was considered endemic to Chilean waters, however, this record confirm its presence in Peru extending its northern distribution limit to San Juan de Marcona, Peru. Morphological and habitat information on this four species is provided, together with live pictures.